Nature, Capital and Neighborhoods: 'Dispossession without Accumulation'? - Kappeler, Aaron; Bigger, Patrick (Antipode, 2011)
The ongoing economic crisis, which originated in the USA and has since spread rapidly to capital markets worldwide, is massive, complex, and many times contradictory. One could say the same for responses to the crisis as governments, firms and multi-national institutions struggle to grasp the full magnitude of the event. This article interrogates the key commodities involved-land, labor and money-and the always-uneasy relations between spaces of social reproduction and capital. Such ambivalence is critical to understanding how new economic realities are formed in light of retreating neoliberalism as markets become destabilized. The analysis provided suggests the commodities involved in the housing crisis are the basis for a countermovement against dispossession.
Geography; Anthropology
Keywords: MARX; Karl; 1818-1883; United States; capital market; capitalism; housing market; international business enterprises; labor; labour; mixed economy; neoliberalism; social aspects

The Commodification of Pollution and a Preemptive Double Movement in Environmental Governance: The Case of Water Quality Trading - Mariola, Matt J. (Organization & Environment, 2011)
The management of environmental pollution has traditionally been accomplished via the regulatory power of the state, but more recently the rise of a new, market-based form of governance has been observed. This article examines the sector of water quality trading, in which caps are placed on surface water pollution and polluters can purchase “offset credits” from farms or other polluters who are under their cap. Using a content analysis of program case studies and federal and state trading rules, the author analyzes this emergent form of environmental governance using an expanded Polanyian framework that he terms the preemptive double movement. Instead of the state reacting to the dangers of a new market form after the fact, here the state uses its existing authority to constrain the market so that further environmental damage does not result. The author describes eight specific regulatory mechanisms that illustrate this preemptive double movement at work.
Sociology; Anthropology; Environmental Studies
Keywords: Polanyi; business & the environment; commodification; double movement; ecological impact; nutrient trading; pollution; water quality management; water quality trading

Redistribution in Aegean Palatial Societies Redistribution and the Political Economy: The Evolution of an Idea - Earle, Timothy (American Journal of Archaeology, 2011)
Whether the Bronze Age Aegean economies can be described as "redistributive" depends on how one defines the term. The concept of redistribution itself has undergone several decades of critical archaeological analysis, much of it stemming from my early work in Polynesia. I consider here how Polanyi's ideas about redistributive economies have been expanded since the 1970s. My review complements the article in this Forum by Nakassis et al. and the contribution by Haistead, who discusses why and how the concept of redistribution still matters in studies of the Minoans and Mycenaeans. To some degree, we all agree: chiefs, and later kings, who sought power in archaic societies did so through many highly variable, contingent, and changing means, all designed to support political-economic strategies based on multiple systems of finance. The Bronze Age Aegean societies provide excellent examples of this process, as demonstrated by the contributors to this Forum.
Anthropology; Archaeology
Keywords: Aegean civilization; Bronze age; chiefdoms; economic aspects; kings & rulers; metals; redistribution; wealth

Redistribution in Aegean Palatial Societies Redistribution in Aegean Palatial Societies: Terminology, Scale, and Significance - Halstead, Paul (American Journal of Archaeology, 2011)
Nakassis et al., in their contribution to this Forum, argue that the term "redistribution" has been used with a range of meanings in the context of the Aegean Bronze Age and so obscures rather than illuminates the emergence and functioning of political economies. They call for detailed empirical investigation rather than reliance on ambiguous idealized types. Lupack and Schon concur, arguing respectively that the palace shared control of the Mycenaean economy with sanctuaries and local communities and that centralized production of craft goods (an,d thus elite strategies of wealth finance) developed late at the palace of Pylos. Pullen finds little archaeological support for Renfrew's extrapolation of centralized redistribution to the Early Bronze Age, while Christakis uses evidence of storage to argue the same for Prepalatial Crete and to play down the scale and importance of elite redistribution in the Minoan palaces. The calls for circumspect use of the term "redistribution" and for detailed empirical investigation are applauded, although these five papers arguably do not all attack the same form of redistribution. This response argues that redistribution sensu Polanyi, Finley, and Killen (i.e., centrally administered movements of goods and services without equivalence of value) retains considerable heuristic value in investigation of both textual and archaeological evidence for Bronze Age political economies.
Anthropology; Archaeology
Keywords: Aegean civilization; Eleia (Greece); Greece; Mycenaean civilization; Pylos site (Eleia; Greece); archaelogy; bronze age; economics; redistribution

Economic Anthropology - Hann, Chris; Hart, Keith (Polity, 2011)
This book is a new introduction to the history and practice of economic anthropology by two leading authors in the field. They show that anthropologists have contributed to understanding the three great questions of modern economic history: development, socialism and one-world capitalism. In doing so, they connect economic anthropology to its roots in Western philosophy, social theory and world history. Up to the Second World War anthropologists tried and failed to interest economists in their exotic findings. They then launched a vigorous debate over whether an approach taken from economics was appropriate to the study of non-industrial economies. Since the 1970s, they have developed a critique of capitalism based on studying it at home as well as abroad. The authors aim to rejuvenate economic anthropology as a humanistic project at a time when the global financial crisis has undermined confidence in free market economics. They argue for the continued relevance of predecessors such as Marcel Mauss and Karl Polanyi, while offering an incisive review of recent work in this field. Economic Anthropology is an excellent introduction for social science students at all levels, and it presents general readers with a challenging perspective on the world economy today.Selected by Choice as a 2013 Outstanding Academic Title
Anthropology
Keywords: cultural anthropology; economic anthropology; social anthropology; sociology - general